5/7(-1x+6)=60/7

Simple and best practice solution for 5/7(-1x+6)=60/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/7(-1x+6)=60/7 equation:


x in (-oo:+oo)

(5/7)*(6-1*x) = 60/7 // - 60/7

(5/7)*(6-1*x)-(60/7) = 0

(5/7)*(6-x)-60/7 = 0

5/7*(6-x)-60/7 = 0

(5/7*7*(6-x))/7-60/7 = 0

5/7*7*(6-x)-60 = 0

-5*x-30 = 0

(-5*x-30)/7 = 0

(-5*x-30)/7 = 0 // * 7

-5*x-30 = 0

-5*x-30 = 0 // + 30

-5*x = 30 // : -5

x = 30/(-5)

x = -6

x = -6

See similar equations:

| -34x^2+34x=0 | | 3m^2+33m+30=0 | | 6(-1x+5)=90 | | -16x^2+34x=0 | | 3/5-3x=4x-312/5 | | 14y^2-14y+5= | | 6r^2+34r+20=0 | | 100/50=(7^2)+5y | | y=2/3(-3)-4 | | 7x-8y=10 | | 2y+4-4y=y+16 | | -3p^2+11p+20=0 | | 36=18*6+b | | -2y+4-4y=y+16 | | 0=-3/7x-3 | | 4/9r=12 | | -1-5x=14x-14 | | 12=-.9a | | 36=44/9*6+b | | y/7+10.1=-1.1 | | 3/4y=33 | | 5x+13=-127-9 | | 3/4y=34 | | z^2+26z+169=0 | | 6y-2-4y=-30 | | 2x+3-6=14 | | -42=6(y+12) | | 42=3*5+b | | 17=9+4a | | 7x+4=-x-84 | | 7x-9=47-7x | | x-7=-13+13x |

Equations solver categories